Students' Understanding of The Equal Sign Based on Their Learning Experience in Arithmetic - Lia Ardiansari; Didi Suryadi; Dadan Dasari (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2023)
The equal sign is an important concept in learning mathematics karena it is used in almost all branches of mathematics, but not many studies in Indonesia have made the equal sign the focus of research. This study aims to explore how students from elementary school to college students understand the equal sign in the context of arithmetic and algebra at school. A qualitative comparative analysis can be used to analyze several cases in complex situations so that it fits the purpose of this study. Participants consisted of 6 elementary school students, 14 junior high school students, 7 high school students and 3 college students in Bandung. The results of the study indicate that the equal sign is still interpreted narrowly as